A day with Alumni / E. Tavasuria Elangovan - Elangovan, E.Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
A Day with Alumni programme was organized by the Faculty of Applied Science (FSG), UiTM Perak Branch, Tapah Campus on May 7, 2018. The sharing session with the UiTM Diploma in Science alumni was an eye opener for the AS120 Diploma in Science students and its staff. The three invited alumni were: En Mazlan Bin Simbak, the Engineering Manager at Petronas LNG, Ir. Zema Zamanee Bin M. Saad, Head Engineer of Penang International Air-port and Lt. Col. Mohd Faizal Bin Md Jani. This programme was launched by Dr. Ahmad Nazib Bin Alias, Head of the Faculty of Applied Sciences, UiTM Perak Branch, Tapah Campus, with the aim to share their experiences and challenges as motivation for the FSG students. The panels shared on how they succeeded with the struggles and obstacles in managing their working lives.